PERSEPSI WARGANET PADA AKUN X @goodghan MENGENAI RESTORAN KAREN’S DINER - Reynaldi Deva Rahmaputra; Herning Suryo S; Fikriana Mahar Rizqi (Solidaritas, 2025)
The use of X as a media can contribute to the recognition of restaurants among consumers, especially X users. Utilization of a X account can provide information, persuade or remind consumers. The purpose of this study was to determine the perception of the @goodghan X account at Karen's Diner restaurant. This type of research is descriptive research. The technique of determining informants using purposive sampling. Data collection using digital documentation. Data analysis techniques using qualitative analysis. The results showed that people's on X perceptions of the @goodghan X account about Karen's Diner restaurant were divided into two things, namely positive perceptions and negative perceptions. Negative perceptions state that Karen's Diner in Indonesia violates the rules, because employees are less polite, excessive anger and employees hold food or drinks from visitors while positive perceptions that Karen's Diner restaurants provide new experiences because they have become part of the modern lifestyle. Keywords: perceptions, x account, restaurant